A Brief Comparison of Religious Legal Systems - Anam, Rifqi Khairul (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2024)
A Brief Comparison of Religious Legal Systems. Religion and law have a close relationship, where religious law provides a moral basis for social order. Religious legal systems have normative characteristics and function as a guideline for their adherents. However, in the increasingly secular modern world, the existence of religious law faces various challenges. Although some religious legal systems still survive, their implementation has different characteristics and often faces challenges of interpretation and adaptation. This study aims to analyze the comparison of religious legal systems in various parts of the world. By examining various sources of religious law, this study will identify similarities and differences in basic principles, the application of law in everyday life, and the challenges faced by each religious legal system in the modern context.